Pulmonary infection with Mycobacterium kansasii in Wales, 1970-9: review of treatment and response. - Banks, J (1983)
Thirty-five patients (88% male) with pulmonary infection caused by Mycobacterium kansasii have been reviewed. Sixty-six per cent had pre-existing lung disease, chronic bronchitis and emphysema accounting for half of the disorders. Unilateral lesions were present in 69% of patients whose chest radiographs were reviewed and 90% had cavitating disease. The development of unilateral or bilateral disease appeared to be independent of any delay in starting treatment. Five patients died while receiving treatment, but none of these deaths was due to M kansasii infection. The remaining 30 patients were successfully treated with drug regimens, all of which included rifampicin and 86% of which included ethambutol. There was 100% sputum conversion, with no relapses after a mean follow-up period of five-and-a-half years. Rifampicin and ethambutol given for a mean period of 15 months appeared to be a non-toxic, effective combination.